The Influence of Classroom Management and the Use of Learning Media on Increasing Student Learning Motivation - HD, Ajeng Alfiyani; Darmawan, Didit (Hikmah, 2023)
This study aims to determine the effect of classroom management and the use of learning media on student learning motivation at SDN Paseseh 01 Tanjungbumi Bangkalan Madura. Learning motivation is a very decisive factor in the educational process, influencing active participation and student enthusiasm. This research investigates the significant influence of effective classroom management and the use of appropriate learning media on student motivation. This research aims to provide insight into improving the quality of education by understanding these key factors. A quantitative approach was used by using questionnaires to collect data on grade VI students of SDN Paseseh 01 Tanjungbumi Bangkalan Madura. Data analysis included regression analysis to determine the extent of the influence of each variable on learning motivation. The research findings show that classroom management, and media use contribute significantly to students' motivation. The study highlights the theoretical and practical implications of these factors, emphasizing their role in creating a conducive learning environment and stimulating intrinsic and extrinsic motivation. The results of this study contribute to a broader understanding of educational practices that positively impact student motivation.